The Relationship between Climate Change, Obesity and Agricultural Policies - Güngör Karakas (Turkish Journal of Agriculture: Food Science and Technology)
The purpose of agricultural policies is to meet the food demand that the society needs. While supports and incentives for agricultural production increase production, they can have negative consequences on climate change. In parallel with the increase in agricultural production and climate change in the world, there has been a serious increase in both food waste and obese numbers recently. While the overproduction effort of agricultural products creates pressure on the environment, it causes obesity and overweight problems. According to the World Health Organization (WHO), Turkey is at the forefront among the countries where there are obese and overweight people. In the 11th Development Plan in Turkey, in 2018 the prevalence of obesity is 30% (for ages 15 and over) in 2023 is targeted to be reduced to 29.1. The aim of this research is to draw attention to the relationship between climate change and obesity and to address the issue within the framework of the 11th Development Plan. Obesity issues for Turkey; since it is important in terms of food security, climate change and agricultural policies, it is necessary to develop political guidance and protection measures in terms of health, economy, education, environment and national security.